Analisis Kontribusi Dan Efektifitas Sumber Pendapatan Asli Daerah Terhadap Pendapatan Asli Daerah Provinsi D.I. Yogyakarta - Choiroel Woestho; Adi Wibowo Noor Fikri; Ari Sulistyowati (UNIVERSITAS MUHAMMADIYAH SUMATERA UTARA, 2023)
The study to analyze the contribution and effectiveness of local taxes and local levies on local revenue. The importance of this analysis is to find out to what extent the contribution of regional taxes and regional levies to local revenue. A high contribution indicates that local revenue comes from activities carried out by the local government. Meanwhile, effectiveness assesses how realization is achieved when compared to revenue targets from local taxes and regional levies. The object in this study is the Province of the Special Region of Yogyakarta, with the data collected from the Regional Revenue and Expenditure Budget (APBD) from the revenue side from 2011 to 2020. The analysis is carried out using descriptive statistics by looking at the results of the comparison of the contribution and effectiveness of local taxes. and local fees. The results obtained indicate that the tax contribution is very good, this is indicated by an average of 81.80%. Meanwhile, the contribution of regional levies has an average value of 2.49% with very poor criteria. For the effectiveness of local taxes, the average is 111.36%, so the criteria are very effective. Meanwhile, the effectiveness of regional retribution is on average 105.76% and is in the very effective criteria.